Designing Of A Conceptual Framework For Assessing The Performance Of Educational Sector Ngos. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper is written with the primary objective to design a framework for assessing the performance of educational sector NGOs. The challenges faced by the NGOs are often very different from the non-profits and hence are difficult to benchmark. Moreover, NGOs have goals and offer services that are more intangible making performance measurement even more challenging. NGOs are very diverse in nature in terms of projects employed, people, beneficiaries as well as strategic goals and objectives. Hence a general framework for performance measurement will not be effective for measuring the performance of these diverse NGOs. This paper will focus on studying and comparing the various frameworks available for measuring the performance of NGOs. After studying these models, the paper will aim towards designing a framework that can effectively assess and measure the performance of the NGOs working in educational sector. The framework will also list down the performance indicators that can be used in measuring the performance of these NGOs.